Towards Cognitive Cultural Didactics in foreign language education - Wirag Andreas (Journal of Language and Cultural Education)
Despite significant advances in the conception of cultural teaching and learning in recent decades, some unresolved problems remain. In Intercultural Learning, the cultures between which learners mediate still appear as bounded, nation-type cultures. In Transcultural Learning, it is unclear how learners could acquire knowledge of an unstable, dynamic, and hybrid object. This article suggests Cognitive Cultural Didactics, which relies on the concept of cognitive scripts, i.e., generic mental representations of everyday activities. Cognitive Cultural Didactics reconsiders cultural learning as the additive acquisition of cognitive scripts that govern everyday interactions in geographically more remote locations. By doing so, the cognitive paradigm can resolve some of the current intercultural and transcultural learning limitations. Moreover, Cognitive Cultural Didactics has essential implications for Anti-Racist Pedagogy. It may serve as an antidote against a racist mindset that puts people into binary categories based on skin colour, place of birth, or parents’ place of birth (‘Us’ vs. ‘Them’).